Quasi‐2D Hybrid Perovskite Formation Using Benzothieno[3, 2‐b]Benzothiophene (BTBT) Ammonium Cations: Substantial Cesium Lead(II) Iodide Black Phase Stabilization. Issue 18 (24th June 2022) - Denis, Paul‐Henry; Mertens, Martijn; Van Gompel, Wouter T. M.; Maufort, Arthur; Mertens, Sigurd; Wei, Zimu; Van Landeghem, Melissa; Gielen, Sam; Ruttens, Bart; Deduytsche, Davy; Detarvernier, Christophe; Lutsen, Laurence; et al.
Abstract: 3D hybrid perovskites (APbX3 ) have made a significant impact on the field of optoelectronic materials due to their excellent performance combined with facile solution deposition and up‐scalable device fabrication. Nonetheless, these materials suffer from environmental instability. To increase material stability, the organic cation (A) is substituted by the non‐volatile cesium cation. However, the desired photoactive cesium lead(II) iodide black phase is metastable in ambient conditions and spontaneously converts into the photo‐inactive yellow δ‐phase. In this work, the black phase is stabilized by the formation of a quasi‐2D perovskite containing a benzothieno[3, 2‐ b ]benzothiophene (BTBT) large organic ammonium cation. Thermal analysis shows that degradation of the butylammonium (BA)‐based quasi‐2D perovskite (BA)2 CsPb2 I7  sets in at ≈130 °C, while (BTBT)2 CsPb2 I7  is phase‐stable until ≈230 °C. Additionally, the (BTBT)2 CsPb2 I7  film does not show any sign of degradation after exposure to 77% Relative Humidity in the dark for 152 days, while (BA)2 CsPb2 I7  degrades in a single day. Photoconductor‐type detectors based on (BTBT)2 CsPb2 I7  demonstrate an increased external quantum efficiency and a similar specific detectivity compared to the BA‐based reference detectors. The results demonstrate the utility of employing a BTBT cation within the organic layer of quasi‐2D perovskites to significantly enhance the stability while maintaining the optoelectronic performance. Abstract : The photoactive black phase of cesium lead(II) iodide is stabilized by the formation of a quasi‐2D perovskite containing a benzothieno[3, 2‐b]benzothiophene (BTBT) large organic ammonium cation. The thermal stability and the moisture stability are significantly enhanced compared to a butylammonium (BA) quasi‐2D perovskite. Photoconductor‐type detectors based on (BTBT)2 CsPb2 I7 demonstrate an increased external quantum efficiency compared to the BA‐based reference detectors.